Modifikasi Media Pembelajaran Trainer Kelistrikan Lampu Depan di SMK Negeri 4 Lhokseumawe - Adi Supardi; Taufiq Taufiq; Islami Fatwa; Dabet, Abu Bakar; Jamadi Rusli (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study aims to develop and modify learning media in the form of a motorcycle headlight electrical trainer to improve the effectiveness of learning for students at State Vocational High School (SMK) 4 Lhokseumawe. Conventional learning media are often less able to provide a real picture of the electrical system of motor vehicles, so it is necessary to develop more representative and interactive aids. The method used in this study is the research and development (R&D) method with the Borg and Gall model. The results of the modification include the addition of visual indicators (LED lights), more systematic wiring, and an electric current disturbance simulation panel. The feasibility test was carried out by media experts, material experts, and limited field trials on vocational high school students. The evaluation results showed that the modified trainer was very suitable for use as a learning medium, in terms of clarity of function, ease of use, and visual appeal. The use of this trainer was able to significantly improve students' understanding of the motorcycle headlight electrical system. .